STUDIES ON FISHERIES POTENTIALS OF DADIN-KOWA RIVER CONTIUUM GOMBE STATE - M, KABIRU; ABUBAKAR, BARA’ATU; S, NAZEEF; ISAH, ZAINAB; HASSAN KIMAN, SUWAIBA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Fisheries Potentials with respect to River morpho-metrics using Morpho-Edaphic Index (MEI), Potential fish yield (Y) and Relative Yield Index (RYI) in Dadin-Kowa River Contiuum Gombe State were carried out for a period of Eighteen month, (October, 2019 to March, 2021). River morpho-metrics were applied to estimate the potential fish yield using morpho-edaphic index (MEI) and above five (5µs/m) in all the sampling stations that is 9.7, 9.6 and 9.14µs/m respectively which is greater than 5 and implies higher fisheries potentials in the river, also Potential fish yield estimates were determined using the relationship Y=23.281*MEI0.447 recorded as 64.3, 64.0 and 62.6Kg/ha which indicate good yield while the relative yield index (RYI) which is the ratio of estimated yield with estimated fish yield was determined using the relationship RYI= Yobs/Yest ×0.75 was found to be 2.7, 1.4 and 1.3Kg. The results of this study showed that the river exploitation level was moderate (RYI≤3). Good, dissolved oxygen levels, good pH, low-levels of pollution, accounted for the high estimates of the fish yield. Therefore, effective management system, implementation of good fishing regulations and practices should be implemented.